Works by Bosniaks in the Field of Logic in the Arabic Language (Prilozi za orijentalnu filologiju, 2017)
This paper gives a survey of the most prominent Bosniak authors, and their writings in Arabic based on authentic manuscripts (around 1,000 manuscript pages). Our focus has been on:- Haşan Kâfi Pruščak and his work: Kafi" s Compendium of Logic (Muhtasar al-Kâfı min al-mantiq, 1580) and Commentary on KafTs Compendium of Logic (Šarh Muhtasar al-Kâfı min al-mantiq, 1583);- Muhamed, the son of Musa, Allamek and his work Commentary on the Shining Treatise (Šarh ar-Risâla aš-šamsiyya, 1626);- Mustafa Ejubović - Šejh Jujo and his four writings: Commentary on Treatise on Logic (Šarh ar-Risâla al-Atîriyya fî al-mantiq, 1682), or, as it was populary called, Commentary on “Isagugi (Šarh Isâğüğî); A Useful Gloss for “Al-Fanâri Notes on Afîri” Treatise on Logic” (Hâsi- ya mufıda li al-Fawâ’id al-Fanâriyya ‘alâ ar-Rişâla fî al-mantiq,1692); New Commentary on the “Shining Treatise” (aš-Šarh al-ğadîd ‘alâ aš- Samsiyya fî al-mantiq, 1690); Commentary on “Education in Logic and Apologhetić’ (Šarh ‘alâ Tahdîb al-mantiq wa al-kalâm, 1706);- Muhamed Čajničanin and his work Revealing Secrets of Commenting on Isagogue (Fath al-asrâr fi šarh Isâğüğî, 1780);- İbrahim, the son of Ramadan, Bosniak and his work Notes on the “Commentary on Shining Treatise” (Tadicjat ‘ala Šarh aš-Šamsiyya, the mid-17tb century);- Fadil Užičanin and his work Commentary on the text “Isagogua” by the mullah Fadil Užičanin (Šarh matn Isâğüğî li mawlâ al-Fâdil Üzi- ccnvalî, the mid-17th century) and- Muhamed, the son of Yusuf, Bosniak and his work Revealing Secrets of Commenting on “Isagoga”, the Science of logic, the second part of the 18th century (Fath al-asrâr fi šarh Isâğüğîfi ‘ ilm al-mantiq).